2013
DOI: 10.1016/j.cell.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Senescence during Mammalian Embryonic Development

Abstract: Cellular senescence disables proliferation in damaged cells, and it is relevant for cancer and aging. Here, we show that senescence occurs during mammalian embryonic development at multiple locations, including the mesonephros and the endolymphatic sac of the inner ear, which we have analyzed in detail. Mechanistically, senescence in both structures is strictly dependent on p21, but independent of DNA damage, p53, or other cell-cycle inhibitors, and it is regulated by the TGF-β/SMAD and PI3K/FOXO pathways. Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,080
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,177 publications
(1,161 citation statements)
references
References 61 publications
(79 reference statements)
35
1,080
3
8
Order By: Relevance
“…Moreover, cumulative lines of evidence are consistent with the point of view that cellular senescence might evolve to optimize embryogenesis, and that its beneficial postnatal functions, to balance tumor suppression and tissue repair or regeneration, could arise and be sustained later in evolution. [1][2][3][4][5][6] We expect that our approach of analyzing evolutionary developmental mechanisms of senescence in zebrafish will accelerate the discovery of new pharmacological interventions in aging, stressmediated disorders and cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cumulative lines of evidence are consistent with the point of view that cellular senescence might evolve to optimize embryogenesis, and that its beneficial postnatal functions, to balance tumor suppression and tissue repair or regeneration, could arise and be sustained later in evolution. [1][2][3][4][5][6] We expect that our approach of analyzing evolutionary developmental mechanisms of senescence in zebrafish will accelerate the discovery of new pharmacological interventions in aging, stressmediated disorders and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Senescence is, therefore, not only a phenomenon observed in the later aging process but is also detectable during embryogenesis of vertebrates; as such, this process might have evolved to regulate embryonic development. However, the underlying genetic and molecular basis in embryonic development and senescence remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…8 ), they can elicit pro-and/or anti-tumorigenic responses, depending on the microenvironment. 12 Finally, recent work has shown that senescence contributes also to tissue remodeling during embryonic development, 21,22 thus highlighting its importance in non-pathological situations. In conjunction with its role in preventing fibrosis, 23,24 these observations also raise the question as to whether fundamentally different mechanistic pathways underlie these different physiological roles of senescence.…”
Section: And Beyondmentioning
confidence: 99%
“…Stress‐induced senescence or age‐independent premature senescence is used to describe the phenomenon in which various stressors, such as oncogenic events and ionizing radiation, instigate cellular dysfunction 6, 7. Additionally, it is becoming evident that senescence also exerts beneficial roles in normal embryonic development and tissue repair processes 8, 9, 10. Mechanically, senescent cells can affect surrounding cells and play active roles in tissue remodeling by secreting such proteins as proinflammatory cytokines, chemokines, and growth factors (senescence‐associated secretory phenotype, SASP) 11.…”
Section: Introductionmentioning
confidence: 99%